A cooperative interaction between NF-kappa B and Sp1 is required for HIV-1 enhancer activation. - Perkins, N D (1993)
The human immunodeficiency virus (HIV-1) long terminal repeat (LTR) contains two binding sites for NF-kappa B in close proximity to three binding sites for the constitutive transcription factor, Sp1. Previously, stimulation of the HIV enhancer in response to mitogens has been attributed to the binding of NF-kappa B to the viral enhancer. In this report, we show that the binding of NF-kappa B is not by itself sufficient to induce HIV gene expression. Instead, a protein-protein interaction must occur between NF-kappa B and Sp1 bound to an adjacent site. Cooperativity both in DNA binding and in transcriptional activation of NF-kappa B and Sp1 was confirmed by electrophoretic mobility shift gel analysis, DNase footprinting, chemical cross-linking and transfection studies in vivo. With a heterologous promoter, we find that the interaction of NF-kappa B with Sp1 is dependent on orientation and position, and is not observed with other elements, including GATA, CCAAT or octamer. An increase in the spacing between the kappa B and Sp1 elements virtually abolishes this functional interaction, which is not restored when these sites are brought back into the same helical position. Several other promoters regulated by NF-kappa B also contain kappa B in proximity to Sp1 binding sites. These findings suggest that an interaction between NF-kappa B and Sp1 is required for inducible HIV-1 gene expression and may serve as a regulatory mechanism to activate specific viral and cellular genes.